Complete mitochondrial genomes of two scaphopod molluscs. Issue 2 (3rd July 2019) - Kocot, Kevin M.; Wollesen, Tim; Varney, Rebecca M.; Schwartz, Megan L.; Steiner, Gerhard; Wanninger, Andreas
Abstract: Complete mitochondrial genomes were determined for two scaphopod molluscs: the dentaliid Antalis entalis and an unidentified Antarctic gadilid. Both genomes are complete except, in Gadilida sp. indet., a short stretch of nad5 was undetermined and trnR could not be annotated. Organization of the Gadilida sp. genome is nearly identical to that previously reported for the gadilid Siphonodentalium whereas trnK, nad5, trnD, nad4, and nad4l are transposed to the opposite strand in the previously published Graptacme genome relative to that of Antalis . Phylogenetic analysis of the 13 protein-coding and 2 rRNA genes recovered Scaphopoda, Gadilida, and Dentaliida monophyletic with maximal support.